NUTRITIONAL STRATEGIES OF SLOVENIAN NATIONAL JUNIOR SWIMMING TEAM - Simič, Vesna; Mohorko, Nina (Annales Kinesiologiae, 2018)
Purpose: The purpose of our study was to assess the nutritional strategies of Slovenian national junior swimming team and compare them with recommendations of clinical sports nutrition. Competitive young swimmers namely have increased energy and nutrient needs compared to general adolescents due to frequent and intense training. Despite some physiological differences from adults, adult sports nutrition recommendations for macronutrients apply to them. Further, literature reports iron, calcium, and vitamin D intake as frequently inadequate. Methods: Nutritional strategies of 19 members of Slovenian national junior swimming team were assessed retrospectively through 3-day food and activity diaries, questionnaires, anthropometric data including bioimpedance analysis. Energy availability (EA), macronutrient intake and timing, iron, calcium and vitamin D intakes, hydration, consumption of sports food and dietary supplement use were evaluated. Results: EA in some of male swimmers and in majority of female swimmers was lower than recommended. Carbohydrate intake was adequate in male swimmers and two thirds of female swimmers. Although average protein intake exceeded the upper recommended limit, some female swimmers did not meet the lower recommended intake limit. Total fat intake was lower than recommended, with saturated fat intake on the upper recommended level. Calcium and iron intake in male swimmers exceeded recommended values, while female swimmers had lower calcium intake than recommended and some had lower iron intake, too. Vitamin D intake was low in all swimmers. Meal timing was adequate in majority of swimmers, who often reached for dietary supplements, mostly omega 3 fatty acids, multivitamins, and magnesium. Conclusions: Low EA in young competitive swimmers is of concern. More successful, personalised nutrition strategies for young competitive swimmers, focusing on higher energy intake and healthy food choices, would contribute to the preservation of their health and development into top performers.